2015
DOI: 10.1002/pros.22988
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone receptor expression during prostate cancer progression suggests a role of this receptor in stromal cell differentiation

Abstract: These results suggest that PR plays an active role in regulating stromal cell phenotypes during prostate cancer progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 17 publications
2
31
0
1
Order By: Relevance
“…Microfilaments are the smallest of the three skeleton structures, are composed of actin and exist in the form of free and globular actin G-actin or F-actin (23). Previous data indicate that the changes in actin polymerization/depolymerization, namely actin skeleton reconstruction, serve important regulatory roles in phenotypes of malignant cells (24). It has been suggested that intervention in cellular skeleton microfilament actin reconstruction may be a functional target of anticancer drugs, and may be regarded as a basis for developing novel antineoplastic drugs (25).…”
Section: Discussionmentioning
confidence: 99%
“…Microfilaments are the smallest of the three skeleton structures, are composed of actin and exist in the form of free and globular actin G-actin or F-actin (23). Previous data indicate that the changes in actin polymerization/depolymerization, namely actin skeleton reconstruction, serve important regulatory roles in phenotypes of malignant cells (24). It has been suggested that intervention in cellular skeleton microfilament actin reconstruction may be a functional target of anticancer drugs, and may be regarded as a basis for developing novel antineoplastic drugs (25).…”
Section: Discussionmentioning
confidence: 99%
“…Ligand-activation of PR plays a critical role in female mammary gland development/homeostasis and other female reproductive organs [10]. Additionally, PR is expressed in prostate tissue and plays an essential role in tissue microenvironment and stromal cell differentiation [17]. PR has two isoforms which have differential roles in normal organ functioning and the balanced expression of both isoforms is critical for normal tissue function [10,18].…”
Section: Class I: the Progesterone Receptor Structural And Functionamentioning
confidence: 99%
“…HMGB1/2 is a protein that increases DNA-protein binding interactions indirectly through increasing the number of contacts of the PR to DNA through dynamic conformational change [21][22][23]. Furthermore, recent evidence suggests a role of PR in prostate cancer progression, specifically through its role in regulating smooth actin muscle (SMAα) in stromal cells [17,24]. PR levels were upregulated after castration in patients with prostate cancer, which could contribute to treatment resistance due to its role in stromal cell differentiation and mobility [17,24].…”
Section: Class I: the Progesterone Receptor Structural And Functionamentioning
confidence: 99%
See 1 more Smart Citation
“…Androgen-growth factors interactions are disordered in androgen-independent PCa and cause sensitization of cancerous cells to low level of androgens in their microenvironment. It was shown that progesterone receptor (PR) signaling plays an active role in changing PCa-associated stromal cell phenotype during the disease progression [57].…”
Section: Prostate Cancermentioning
confidence: 99%